An Insight Extraction System on BioMedical Literature with Deep Neural Networks - He, Hua; Ganjam, Kris; Jain, Navendu; Lundin, Jessica; White, Ryen W.; Lin, Jimmy (Conference on Empirical Methods in Natural Language Processing (EMNLP), 2017)
Mining biomedical text offers an opportunity to automatically discover important facts and infer associations among them. As new scientific findings appear across a large collection of biomedical publications, our aim is to tap into this literature to automate biomedical knowledge extraction and identify important insights from them. Towards that goal, we develop a system with novel deep neural networks to extract insights on biomedical literature. Evaluation shows our system is able to provide insights with competitive accuracy of human acceptance and its relation extraction component outperforms previous work.